2017
DOI: 10.1371/journal.pone.0181319
|View full text |Cite
|
Sign up to set email alerts
|

Presentation at computed tomography (CT) scan of the thorax and first year diagnostic and treatment utilization among patients diagnosed with lung cancer

Abstract: BackgroundAs Medicare expands the use of computed tomography (CT) for diagnosing lung cancer, there is increased opportunity to diagnose lung cancer in asymptomatic patients. This descriptive study characterizes the disease-specific diagnostic and treatment services that patients with a positive diagnosis following CT received, stratified by presentation at CT.MethodsPatients who were diagnosed with lung cancer following CT in 2013, had no history of lung cancer, survived at least 1 year, were aged 55–80 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A lung nodule flagger can potentially change the rate at which lab tests and biopsies are conducted and the rate at which patients receiving images progress to receiving surgery, radiation therapy, or chemotherapy. Prior research has shown that asymptomatic patients which are diagnosed with lung cancer have very different patterns of downstream service utilization from symptomatic patients (4). To the extent that AI enables patients to be more likely to receive diagnoses before they progress to being symptomatic, there may be a reduction in the utilization of downstream services.…”
Section: Downstream Costsmentioning
confidence: 99%
“…A lung nodule flagger can potentially change the rate at which lab tests and biopsies are conducted and the rate at which patients receiving images progress to receiving surgery, radiation therapy, or chemotherapy. Prior research has shown that asymptomatic patients which are diagnosed with lung cancer have very different patterns of downstream service utilization from symptomatic patients (4). To the extent that AI enables patients to be more likely to receive diagnoses before they progress to being symptomatic, there may be a reduction in the utilization of downstream services.…”
Section: Downstream Costsmentioning
confidence: 99%
“…In China, the morbidity (20.48%) and mortality (40.71%) of lung cancer rank as the first among all malignant tumors, representing a great threat to public health ( 2 ). Studies have demonstrated that non-small cell lung cancer (NSCLC), as the main clinical pathological type, accounts for ~90% of lung cancer cases ( 3 5 ). Due to the difficulty for the early diagnosis of NSCLC, distant metastasis occurs in ~40% of patients at the first diagnosis, whereas 50% of patients in the treatment process suffer from tumor metastasis ( 6 ).…”
Section: Introductionmentioning
confidence: 99%